Viscous solid electrolyte coating diaphragm as well as preparation method and application thereof
By using a viscous solid electrolyte to coat the separator on the separator of a metallic lithium battery, including a base film, a solid electrolyte coating and a polydopamine coating, the problem of battery short circuit caused by the growth of lithium dendrites is solved and a higher cycle is achieved. longevity and stability.
Patent Information
- Application Number
- CN202411471424.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
Metal lithium batteries are prone to lithium dendrites to grow under large currents, resulting in puncture of the separator and short circuit of the battery.
Adopt a viscous solid electrolyte coating, including base membrane, solid electrolyte coating and polynabine coating. It provides strong adhesion for polynamine coatings to prevent the lithium ions from excessive deposits in the local area and inhibit lithium branches in the local area and inhibit lithium branches The generation of crystal.
Effectively suppress the generation of lithium branches, avoid the uneven deposition of lithium, enhance the mechanical strength of the diaphragm, reduce thermal contraction at high temperature, and improve the cycle life and stability of the battery.
Smart Images

Figure BDA0005094894360000091 
Figure BDA0005094894360000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a viscous solid electrolyte coated diaphragm, a preparation method thereof and an application thereof. Background Art
[0002] Metal lithium electrodes can provide extremely high specific capacity, thereby improving the overall mass energy density and volume energy density of the battery. However, when metal foil is used directly as the negative electrode, the battery faces the problem of lithium dendrite growth under large current. The dendrites will pierce the diaphragm and cause the battery to short circuit.
[0003] As a new technology, solid electrolyte coated diaphragm has shown its unique advantages. Solid electrolyte has high ionic conductivity and can enhance the wettability of electrolyte to diaphragm, thereby enhancing ion transport in electrolyte. More importantly, the hard texture of solid electrolyte can prevent lithium dendrites from piercing the diaphragm. However, the distance between solid electrolyte coating and metal electrode is far, which cannot suppress the formation of dendrites on metal electrode. In addition, there are still gaps in solid electrolyte coating for metal dendrites to pass through. Therefore, by further coating a polymer coating on inorganic coating or using a polymer to coat inorganic solid electrolyte, the diaphragm can produce adhesion to positive and negative electrodes, which can mechanically suppress the uneven deposition of lithium and the formation of lithium dendrites. However, the above scheme still has many problems. For example, due to its own flexibility, high molecular polymer can generate viscosity through strong van der Waals force. However, this viscosity depends on the physical contact distance and is still weak, which is not enough to effectively suppress dendrites. In the process of configuring the polymer-coated solid electrolyte into a slurry and coating the diaphragm, a binder is required to enhance the adhesion. However, the binder will further coat the solid electrolyte, making it impossible for the polymer coating layer to provide the expected function.
[0004] Therefore, providing a separator that can effectively inhibit the growth of metal negative electrode dendrites becomes a problem to be solved. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a viscous solid electrolyte coated diaphragm and its preparation method and application. The viscous solid electrolyte coated diaphragm provided by the present invention can prevent the excessive deposition of lithium ions in local areas and induce the formation of lithium dendrites.
[0006] The present invention provides a solid electrolyte coated diaphragm having viscosity, comprising:
[0007] Basement membrane;
[0008] A solid electrolyte coating disposed on the surface of the base film;
[0009] A polydopamine coating is disposed on the surface of the solid electrolyte coating.
[0010] Preferably, the base film is selected from at least one of a polypropylene film, a polyethylene film, and a non-woven fabric membrane.
[0011] Preferably, the solid electrolyte in the solid electrolyte coating is at least one of LLZO, LLTO, and LATP; the particle size of the solid electrolyte is 300 to 500 nm;
[0012] The thickness of the solid electrolyte coating is 1 to 3 μm.
[0013] Preferably, the thickness of the polydopamine coating is 10 to 20 nm.
[0014] The present invention also provides a method for preparing the above-mentioned viscous solid electrolyte coated diaphragm, comprising the following steps:
[0015] Coating a solid electrolyte slurry on the surface of the base film to obtain a solid electrolyte coating;
[0016] A dopamine aqueous solution is coated on the surface of the solid electrolyte coating, and after drying, a sticky solid electrolyte coating diaphragm is obtained.
[0017] Preferably, the solid electrolyte slurry comprises:
[0018] 30-40 parts of solid electrolyte;
[0019] 1-2 parts of adhesive;
[0020] 0.5-0.7 parts of wetting agent;
[0021] 60-70 parts of solvent;
[0022] The solid content of the solid electrolyte slurry is 30wt% to 40wt%;
[0023] The binder is selected from at least one of polyacrylate, carboxymethyl acrylate, carboxymethyl cellulose salt, and PVDF binders;
[0024] The wetting agent is selected from at least one of sodium lauryl sulfate, condensation products of fatty alcohols and ethylene oxide, acetylenic glycols, and polyether siloxanes;
[0025] The solvent is deionized water.
[0026] Preferably, the concentration of the dopamine aqueous solution is 0.05-0.1 mol / L.
[0027] Preferably, the drying temperature is 50-60°C.
[0028] Preferably, after the drying, the moisture content of the diaphragm is controlled below 1000 ppm.
[0029] The present invention also provides a secondary battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is metallic lithium, and the separator is selected from the above-mentioned viscous solid electrolyte coated separator.
[0030] Compared with the prior art, the present invention provides a viscous solid electrolyte coated diaphragm, comprising: a base film; a solid electrolyte coating disposed on the surface of the base film; and a polydopamine coating disposed on the surface of the solid electrolyte coating. In the viscous solid electrolyte coated diaphragm provided by the present invention, the solid electrolyte coated diaphragm can enhance the mechanical strength of the diaphragm and reduce the thermal shrinkage of the diaphragm at high temperatures. In addition, the solid electrolyte coating can promote the wetting of the diaphragm by the electrolyte and the effect of replenishing lithium. The polydopamine coating can provide adhesion, so that the diaphragm can be uniformly adhered to the metal lithium negative electrode, weakening the adverse effects of crosstalk between the positive and negative electrodes. The strong adhesion will avoid uneven deposition of lithium and prevent the excessive deposition of lithium ions in local areas from inducing the formation of lithium dendrites. Using the diaphragm with a solid electrolyte and a polydopamine double-layer coating provided by the present invention as a battery separator, the obtained metal lithium battery can operate stably at a higher current density and exhibit a longer cycle life. DETAILED DESCRIPTION
[0031] The present invention provides a solid electrolyte coated diaphragm having viscosity, comprising:
[0032] Basement membrane;
[0033] A solid electrolyte coating disposed on the surface of the base film;
[0034] A polydopamine coating is disposed on the surface of the solid electrolyte coating.
[0035] The sticky solid electrolyte coated diaphragm provided by the present invention comprises a base film, and the base film is a porous base film. Preferably, the porous base film is selected from at least one of a polypropylene film, a polyethylene film, and a non-woven fabric diaphragm.
[0036] The sticky solid electrolyte coated diaphragm provided by the present invention also includes a solid electrolyte coating arranged on the surface of the base film, and the solid electrolyte in the solid electrolyte coating is at least one of LLZO, LLTO, and LATP; the particle size of the solid electrolyte is 300 to 500 nm, which can be 300, 350, 400, 450, 500, or any value between 300 and 500 nm.
[0037] The thickness of the solid electrolyte coating is 1 to 3 μm, and can be 1, 1.5, 2, 2.5, 3, or any value between 1 and 3 μm.
[0038] The viscous solid electrolyte coated diaphragm provided by the present invention further comprises a polydopamine coating disposed on the surface of the solid electrolyte coating. The thickness of the polydopamine coating is 10 to 20 nm. It can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or any value between 10 and 20 nm.
[0039] In the present invention, the composite coating formed by the solid electrolyte coating and the polydopamine layer can be disposed on one side or both sides of the base film.
[0040] The present invention also provides a method for preparing the above-mentioned viscous solid electrolyte coated diaphragm, comprising the following steps:
[0041] Coating a solid electrolyte slurry on the surface of the base film to obtain a solid electrolyte coating;
[0042] A dopamine aqueous solution is coated on the surface of the solid electrolyte coating, and after drying, a sticky solid electrolyte coating diaphragm is obtained.
[0043] The present invention first configures a solid electrolyte slurry, wherein the solid electrolyte slurry comprises:
[0044] 30-40 parts of solid electrolyte;
[0045] 1-2 parts of adhesive;
[0046] 0.5-0.7 parts of wetting agent;
[0047] 60-70 parts of solvent.
[0048] The solid electrolyte slurry provided by the present invention includes 30 to 40 parts of solid electrolyte, which can be 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, or any value between 30 and 40 parts.
[0049] The solid electrolyte slurry provided by the present invention further comprises 1 to 2 parts of a binder, which may be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, or any value between 1 and 2 parts. The binder is selected from at least one of polyacrylate, carboxymethyl acrylate, carboxymethyl cellulose salt, and PVDF binders.
[0050] The solid electrolyte slurry provided by the present invention further comprises 0.5 to 0.7 parts of a wetting agent, which may be 0.5, 0.55, 0.6, 0.65, 0.7, or any value between 0.5 and 0.7 parts. The wetting agent is selected from at least one of sodium lauryl sulfate, a condensate of a fatty alcohol and ethylene oxide, acetylenic glycols, and polyether siloxane.
[0051] The solid electrolyte slurry provided by the present invention further comprises 60 to 70 parts of a solvent, which may be 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, or any value between 60 and 70. The solvent is preferably deionized water.
[0052] The solid content of the solid electrolyte slurry is 30wt% to 40wt%, and can be 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, or any value between 30wt% and 40wt%.
[0053] In the present invention, unless otherwise specified, the parts of raw materials used are parts by mass.
[0054] Then, the solid electrolyte slurry is coated on the surface of the base film to obtain a solid electrolyte coating. The present invention has no special limitation on the coating method, and any coating method known to those skilled in the art can be used.
[0055] Then, a dopamine aqueous solution is coated on the surface of the solid electrolyte coating, and after drying, a sticky solid electrolyte coating membrane is obtained.
[0056] The concentration of the dopamine aqueous solution is 0.05-0.1 mol / L, and can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or any value between 0.05 and 0.1 mol / L.
[0057] The present invention has no particular limitation on the coating method, and preferably the dopamine aqueous solution is sprayed onto the surface of the solid electrolyte coating.
[0058] The drying temperature is 50-60° C. After the drying, the moisture content of the separator is controlled to be below 1000 ppm.
[0059] Dopamine monomers can be polymerized into polydopamine under the catalysis of basic Lewis sites on the surface of solid electrolyte particles.
[0060] Among them, dopamine monomers in the dopamine aqueous solution can quickly polymerize into a coating layer with uniform thickness in an alkaline environment, and a large number of Lewis basic sites are evenly distributed on the surface of the solid electrolyte. The confinement effect of these Lewis basic sites can catalyze the polymerization of dopamine monomers on the surface of the solid electrolyte particles. The resulting polydopamine layer can achieve strong adhesion to organic and inorganic substrates in a liquid environment.
[0061] Therefore, the polydopamine coating can provide adhesion, allowing the diaphragm to adhere evenly to the metallic lithium negative electrode, weakening the adverse effects of crosstalk between the positive and negative electrodes. The strong adhesion will avoid uneven deposition of lithium and prevent the excessive deposition of lithium ions in local areas from inducing the formation of lithium dendrites.
[0062] The present invention also provides a secondary battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is metallic lithium, and the separator is selected from the above-mentioned viscous solid electrolyte coated separator.
[0063] The present invention provides a coating scheme for a viscous diaphragm, which can constrain uniform metal deposition during charging by adhesion of the diaphragm to the metal negative electrode, avoid stress accumulation to induce metal dendrites, and prevent the battery from being affected by dendrites and causing short circuits or even thermal runaway. The in-situ polymerization scheme provided by the present invention is simple and easy to operate, and can effectively control the coating layer thickness by controlling the concentration of the dopamine aqueous solution, and is compatible with existing industrial diaphragm coating schemes.
[0064] In order to further understand the present invention, the viscous solid electrolyte coated diaphragm provided by the present invention and its preparation method and application are described below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0065] Embodiment 1:
[0066] 1. Diaphragm coating:
[0067] The first layer of solid electrolyte coating: 30 parts of LLZO solid electrolyte and 70 parts of deionized water are dispersed into a slurry by a disperser, wherein the LLZO particle size is 300-500nm, and the solid content is 30wt%. 2 parts of binder (polyacrylate polymer, purchased from Hunan Gaorui Power Materials Co., Ltd., model GR506) and 0.7 parts of wetting agent (sodium dodecyl sulfate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) are added to the slurry in turn. After mixing evenly, it is applied to one side of the PE diaphragm by roller coating, and the coating thickness is controlled to be 2μm.
[0068] The second layer of polydopamine coating is prepared by dissolving dopamine in water into a 0.1 mol / L solution, which is sprayed on the solid electrolyte coating of the above-mentioned diaphragm. The diaphragm is placed in a 60°C oven until the moisture content of the diaphragm is controlled below 1000 ppm. The thickness is controlled at 20 nm after polymerization.
[0069] 2. Assembly of button cells with lithium metal as negative electrode:
[0070] NCM811 positive electrode active material, conductive carbon black and binder were added to NMP in a weight ratio of 8:1:1 and mixed evenly. The positive electrode slurry was evenly coated on the surface of aluminum foil, and further dried, rolled and cut to obtain positive electrode sheets. The negative electrode sheets were lithium sheets with a thickness of 0.5 mm.
[0071] The lithium sheet, the above-mentioned separator, the electrolyte, and the positive electrode sheet are assembled in sequence in a button battery shell.
[0072] Embodiment 2:
[0073] The button cell assembly method of Example 2 is the same as that of Example 1, and the diaphragm coating scheme used is as follows:
[0074] The first layer of solid electrolyte coating: 30 parts of LLZO solid electrolyte and 70 parts of deionized water are dispersed by a disperser, wherein the LLZO particle size is 300-500nm, and the solid content is 30wt%. 2 parts of binder (polyacrylate polymer, purchased from Hunan Gaorui Power Materials Co., Ltd., model GR506) and 0.7 parts of wetting agent (sodium dodecyl sulfate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) are added to the slurry in turn. After mixing evenly, it is applied on one side of the PE diaphragm by roller coating, and the coating thickness is controlled to be 2μm.
[0075] The second layer of polydopamine coating is prepared by dissolving dopamine in water into a 0.05 mol / L solution, which is sprayed on the solid electrolyte coating of the above-mentioned diaphragm. The diaphragm is placed in an oven at 60°C until the moisture content of the diaphragm is controlled below 1000 ppm. The thickness is controlled at 10 nm after polymerization.
[0076] The assembly procedure of the button cell with metallic lithium as the negative electrode is the same as that in Example 1.
[0077] Example 3
[0078] The button cell assembly method of Example 3 is the same as that of Example 1, and the diaphragm coating scheme used is as follows:
[0079] The first layer of solid electrolyte coating: 30 parts of LLZO solid electrolyte and 70 parts of deionized water are dispersed by a disperser, wherein the LLZO particle size is 300-500nm, and the solid content is 30wt%. 2 parts of binder (polyacrylate polymer, purchased from Hunan Gaorui Power Materials Co., Ltd., model GR506) and 0.7 parts of wetting agent (sodium dodecyl sulfate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) are added to the slurry in turn. After mixing evenly, it is applied on one side of the PE diaphragm by roller coating, and the coating thickness is controlled to be 2μm.
[0080] The second layer of polydopamine coating is prepared by dissolving dopamine in water into a 0.08 mol / L solution, which is sprayed on the solid electrolyte coating of the above-mentioned diaphragm. The diaphragm is placed in a 60°C oven until the moisture content of the diaphragm is controlled below 1000 ppm. The thickness is controlled at 15 nm after polymerization.
[0081] The assembly procedure of the button cell with metallic lithium as the negative electrode is the same as that in Example 1.
[0082] Example 4
[0083] The button cell assembly method of Example 4 is the same as that of Example 1, and the diaphragm coating scheme used is as follows:
[0084] The first layer of solid electrolyte coating: 30 parts of LLTO solid electrolyte and 70 parts of deionized water are dispersed by a disperser, wherein the LLTO particle size is 300-500nm, and the solid content is 30wt%. 2 parts of binder (polyacrylate polymer, purchased from Hunan Gaorui Power Materials Co., Ltd., model GR506) and 0.7 parts of wetting agent (sodium dodecyl sulfate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) are added to the slurry in turn. After mixing evenly, it is applied on one side of the PE diaphragm by roller coating, and the coating thickness is controlled to be 2μm.
[0085] The second layer of polydopamine coating is prepared by dissolving dopamine in water into a 0.1 mol / L solution, which is sprayed on the solid electrolyte coating of the above-mentioned diaphragm. The diaphragm is placed in a 60°C oven until the moisture content of the diaphragm is controlled below 1000 ppm. The thickness is controlled at 20 nm after polymerization.
[0086] The assembly procedure of the button cell with metallic lithium as the negative electrode is the same as that in Example 1.
[0087] Example 5
[0088] The button cell assembly method of embodiment 5 is the same as that of embodiment 1, and the diaphragm coating scheme used is as follows:
[0089] The first layer of solid electrolyte coating: 30 parts of LLZO solid electrolyte and 70 parts of deionized water are dispersed by a disperser, wherein the LLTO particle size is 300-500nm, the solid content is 30wt%, and 2 parts of binder (polyacrylate polymer, purchased from Hunan Gaorui Power Materials Co., Ltd., model GR506) and 0.7 parts of wetting agent (sodium dodecyl sulfate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) are added to the slurry in turn. After mixing evenly, it is applied on one side of the PE diaphragm by roller coating, and the coating thickness is controlled to be 3μm.
[0090] The second layer of polydopamine coating is prepared by dissolving dopamine in water into a 0.1 mol / L solution, which is sprayed on the solid electrolyte coating of the above-mentioned diaphragm. The diaphragm is placed in a 60°C oven until the moisture content of the diaphragm is controlled below 1000 ppm. The thickness is controlled at 20 nm after polymerization.
[0091] The assembly procedure of the button cell with metallic lithium as the negative electrode is the same as that in Example 1.
[0092] Comparative Example 1:
[0093] Comparative Example 1 is the same as the button cell assembly method of Example 1, but the diaphragm coating scheme used is as follows:
[0094] 30 parts of LLTO solid electrolyte and 70 parts of deionized water were dispersed by a disperser, wherein the LLTO particle size was 300-500nm and the solid content was 30wt%. 2 parts of binder (polyacrylate polymer, purchased from Hunan Gaorui Power Materials Co., Ltd., model GR506) and 0.7 parts of wetting agent (sodium dodecyl sulfate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) were added to the slurry in sequence. After mixing evenly, it was coated on one side of the PE diaphragm by roller coating, and the coating thickness was controlled to be 2μm.
[0095] The assembly procedure of the button cell with metallic lithium as the negative electrode is the same as that in Example 1.
[0096] Comparative Example 2:
[0097] The button cell assembly method of Comparative Example 2 is the same as that of Example 1, and the diaphragm coating scheme used is as follows:
[0098] Dopamine was dissolved in water to prepare a 0.1 mol / L solution, which was sprayed on a PE diaphragm. The diaphragm was placed in an oven at 60°C until the moisture content of the diaphragm was controlled below 1000 ppm. The thickness was controlled to be 20 nm after polymerization.
[0099] The assembly procedure of the button cell with metallic lithium as the negative electrode is the same as that in Example 1.
[0100] Comparative Example 3
[0101] Comparative Example 3 is the same as the button cell assembly method of Example 1, and the diaphragm coating scheme used is as follows:
[0102] The first layer of solid electrolyte coating: LLZO solid electrolyte slurry is dispersed by a disperser, wherein the LLZO particle size is 300-500nm, the solid content is 30-40wt%, 3wt% of the solid mass of the binder and 0.5wt% of the total mass of the slurry are added to the slurry in sequence, and after mixing evenly, it is applied to one side of the PE diaphragm by roller coating, and the coating thickness is controlled to be 2μm.
[0103] The second layer of polydopamine coating is prepared by dissolving dopamine in water into a 0.04 mol / L solution, which is sprayed on the solid electrolyte coating of the above-mentioned diaphragm. The diaphragm is placed in a 60°C oven until the moisture content of the diaphragm is controlled below 1000 ppm. The thickness is controlled at 5 nm after polymerization.
[0104] The assembly procedure of the button cell with metallic lithium as the negative electrode is the same as that in Example 1.
[0105] Comparative Example 4
[0106] Comparative Example 4 is the same as the button cell assembly method of Example 1, and the diaphragm coating scheme used is as follows:
[0107] The first layer of solid electrolyte coating: 30 parts of LLZO solid electrolyte and 70 parts of deionized water are dispersed by a disperser, wherein the LLZO particle size is 300-500nm, and the solid content is 30wt%. 2 parts of binder (polyacrylate polymer, purchased from Hunan Gaorui Power Materials Co., Ltd., model GR506) and 0.7 parts of wetting agent (sodium dodecyl sulfate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) are added to the slurry in turn. After mixing evenly, it is applied on one side of the PE diaphragm by roller coating, and the coating thickness is controlled to be 2μm.
[0108] The second layer of polydopamine coating is prepared by dissolving dopamine in water into a 0.12 mol / L solution, which is sprayed on the solid electrolyte coating of the above-mentioned diaphragm. The diaphragm is placed in a 60°C oven until the moisture content of the diaphragm is controlled below 1000 ppm. The thickness is controlled at 25 nm after polymerization.
[0109] The assembly procedure of the button cell with metallic lithium as the negative electrode is the same as that in Example 1.
[0110] Comparative Example 5
[0111] Comparative Example 5 is the same as the button cell assembly method of Example 1, and the diaphragm coating scheme used is as follows:
[0112] 30 parts of LLZO solid electrolyte and 70 parts of deionized water were dispersed by a disperser, wherein the LLZO particle size was 300-500nm and the solid content was 30wt%. 2 parts of binder (polyacrylate polymer, purchased from Hunan Gaorui Power Material Co., Ltd., model GR506), 0.7 parts of wetting agent (sodium dodecyl sulfate, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) and 0.5 parts of dopamine solution (concentration of 0.1 mol / L) were added to the slurry in turn. After mixing evenly, they were coated on one side of the PE diaphragm by roller coating. The diaphragm was placed in an oven at 60°C until the moisture content of the diaphragm was controlled below 1000ppm and the coating thickness was controlled to 2μm.
[0113] The assembly procedure of the button cell with metallic lithium as the negative electrode is the same as that in Example 1.
[0114] The performance test was performed on the batteries of the above embodiments and comparative examples, and the specific test method is as follows:
[0115] Battery cycle stability test: At 25°C, the battery is charged and discharged at different current rates, and the number of cycles before the capacity drops rapidly or short circuits is recorded as the cycle life. In order to eliminate the test impact caused by the stripping of negative metal lithium during discharge, each group of cycles is discharged at a current of 0.5C, and cycle tests are performed at charging currents of 0.5C, 1C, and 5C respectively.
[0116] See Table 1, which is a statistical table of button battery cycle life and capacity retention rate after 100 cycles. To ensure the credibility of the data, 3 batteries are tested for each current gradient, and the middle value is collected in the table below.
[0117] Table 1
[0118]
[0119]
[0120] Comparing the cycle life and 100-cycle capacity retention rate of the battery, the battery in Example 1 can be cycled for more than 300 cycles at different current rates, and has an extremely high capacity retention rate after cycling 100 cycles at a high rate of 5C, which means that the double-layer coating can effectively inhibit the formation of lithium dendrites, reduce dead lithium, improve the capacity retention rate, and prevent lithium dendrites from piercing the diaphragm and causing a battery short circuit.
[0121] Comparative Examples 1 and 2 respectively use diaphragms coated with only LLZO solid electrolyte and polydopamine. At high rates, the dendrite growth rate is accelerated, the battery is prone to short circuit, and the large amount of dead lithium produced seriously affects the capacity retention. This means that the synergistic effect of the double-layer coating can effectively improve the working stability of lithium metal batteries. The LLZO coating enhances the rigidity of the diaphragm and provides a certain lithium supplement effect, which is conducive to increasing the capacity. The viscosity of the polydopamine layer can make the diaphragm effectively adhere to the surface of the metal lithium, and the stress generated is conducive to the uniform deposition of lithium, thereby reducing the formation of lithium dendrites.
[0122] The diaphragm used in Comparative Example 3 contains a thinner polydopamine coating. Although it maintains a good 100-cycle capacity retention rate, the growth of lithium dendrites will seriously affect the cycle life. This may be because the polydopamine coating is too thin to maintain a continuous morphology, and the effect on the uniform deposition of lithium is weakened.
[0123] The diaphragm used in Comparative Example 4 contains a thicker polydopamine coating, which forms a continuous coating and significantly reduces the air permeability of the diaphragm, affecting the transport of lithium ions through the diaphragm, thereby forming severe concentration polarization at the negative electrode interface to form dead lithium and reduce the cycle life.
[0124] In Comparative Example 5, dopamine solution was added to the solid electrolyte slurry. The battery using this separator could be cycled for more than 300 times at various rates, but the capacity retention rate was lower than that of Examples 1 to 3, indicating that the uncontrolled growth of lithium dendrites produced more dead lithium, thereby reducing the cycle life. This further indicates that the viscosity of the polydopamine coating can effectively inhibit the growth of lithium dendrites.
[0125] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A viscous solid electrolyte coated diaphragm, characterized in that: include: Basement membrane; A solid electrolyte coating disposed on the surface of the base film; A polydopamine coating is disposed on the surface of the solid electrolyte coating.
2. The diaphragm according to claim 1, characterized in that The base film is selected from at least one of a polypropylene film, a polyethylene film, and a non-woven fabric separator.
3. The diaphragm according to claim 1, characterized in that The solid electrolyte in the solid electrolyte coating is at least one of LLZO, LLTO, and LATP; the particle size of the solid electrolyte is 300 to 500 nm; The thickness of the solid electrolyte coating is 1 to 3 μm.
4. The diaphragm according to claim 1, characterized in that The thickness of the polydopamine coating is 10-20 nm.
5. A method for preparing a viscous solid electrolyte coated diaphragm as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Coating a solid electrolyte slurry on the surface of the base film to obtain a solid electrolyte coating; A dopamine aqueous solution is coated on the surface of the solid electrolyte coating, and after drying, a sticky solid electrolyte coating diaphragm is obtained.
6. The preparation method according to claim 5, characterized in that: The solid electrolyte slurry comprises: 30-40 parts of solid electrolyte; 1-2 parts of adhesive; 0.5-0.7 parts of wetting agent; 60-70 parts of solvent; The solid content of the solid electrolyte slurry is 30wt% to 40wt%; The binder is selected from at least one of polyacrylate, carboxymethyl acrylate, carboxymethyl cellulose salt, and PVDF binders; The wetting agent is selected from at least one of sodium lauryl sulfate, condensation products of fatty alcohols and ethylene oxide, acetylenic glycols, and polyether siloxanes; The solvent is deionized water.
7. The preparation method according to claim 5, characterized in that: The concentration of the dopamine aqueous solution is 0.05-0.1 mol / L.
8. The preparation method according to claim 5, characterized in that: The drying temperature is 50-60°C.
9. The preparation method according to claim 5, characterized in that: After the drying, the moisture content of the diaphragm is controlled below 1000 ppm.
10. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is metallic lithium and the separator is selected from the viscous solid electrolyte coated separator according to any one of claims 1 to 4.
Citation Information
Patent Citations
Coating diaphragm with high flame retardance and lithium dendrite growth inhibition function and preparation method of coating diaphragm
CN114374051A
Modified polyolefin composite diaphragm
CN219832937U
A separator, the manufacturing method thereof, and electrochemical device containing the same
KR1020130099463A
Apparatus, system and method for encouraging content participation based on user interaction including various contents such as aquarium
KR102740570B1
Modified ceramic composite separator and manufacturing method thereof
US20180226624A1
Cited By
Solid electrolyte coating liquid, solid electrolyte coating diaphragm, secondary battery and preparation method
CN121939012A